Validity of distress thermometer for caregivers of cancer patients in Saudi Arabia - Muneera A. AlKhorayef; Manal M. AlJurbua; Nouf A. AlHussaini; Reema A. AlMasoud; Ajeed M. Al Rashoud; Abdulillah M. Al Rashoud; Abdulmajeed A. Zarbah; Fahad D. Alosaimi (PLoS ONE, 2026)
Background Caregivers of cancer patients often face high levels of psychological distress, yet routine screening in clinical settings remains limited. The Distress Thermometer (DT) offers a brief and practical tool for identifying distress; however, its use among caregivers in Saudi Arabia has not been well studied. This study aims to validate the Arabic version of the DT in this population, determine its optimal cutoff scores, and explore associations with anxiety, depression, and demographic factors. Methods A cross-sectional study was conducted at King Saud University Medical City (KSUMC), enrolling 275 caregivers. Participants completed the Arabic versions of the DT and the Hospital Anxiety and Depression Scale (HADS). Receiver Operating Characteristic (ROC) curve analysis was used to assess the DT’s predictive validity for anxiety and depression, while multivariable regression identified predictors of distress. Results Clinically significant distress (DT ≥ 5) was reported by 44% of caregivers. Anxiety symptoms were present in 24%, and depression in 25%. DT scores were strongly correlated with HADS total (ρ = 0.618), HADS-anxiety (ρ = 0.537), and HADS-depression (ρ = 0.562) scores (all p < 0.001). The DT demonstrated excellent predictive validity, with an area under the curve (AUC) of 0.816 for anxiety and 0.818 for depression. The optimal cutoff scores were ≥5.5 and ≥6.5 for anxiety and depression, respectively. Female caregivers and those supporting patients with advanced-stage cancer reported significantly higher distress. Conclusion The Arabic version of the DT is a valid and practical tool for identifying psychological distress among cancer caregivers in Saudi Arabia. Its brevity makes it suitable for routine clinical use. Further research is necessary to develop effective distress screening and intervention programs, particularly for caregivers of patients with advanced cancer, to ensure timely psychological support.